2016
DOI: 10.1016/j.carbpol.2016.05.093
|View full text |Cite
|
Sign up to set email alerts
|

Starch, inulin and maltodextrin as encapsulating agents affect the quality and stability of jussara pulp microparticles

Abstract: The influence of encapsulating carbohydrates (EC) with varying properties on the technological and functional properties of jussara pulp microparticles produced by spray drying were evaluated using experimental design. Microparticles produced with sodium octenyl succinate (OSA) starch at 0.5 core to EC ratio and with mixtures of inulin and maltodextrin at 1.0 and 2.0 core to EC ratio showed darker color, and higher anthocyanins contents and antioxidant activity. Seven microparticles showing high water solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 33 publications
2
39
1
5
Order By: Relevance
“…[15] Microencapsulation of sour cherries using maltodextrin and gum arabic with core to coating ratio 1 : 20 resulted in higher encapsulation efficiencies and smaller particle size than ration 1 : 10. [16] Microencapsulation of ascorbic acid using maltodextrin showed only 7% of ascorbic acid reduction in sample after stirage for 60 days at 28oC temperature. maltodextrin showed higer protection of bioactive compound compare with gum arabic, gum Arabic-modified starch (GA-MS), modified starch-chitosan (MS-CH) and modified starchmaltodextrin-chitosan (MS-MD-CH) (Chranioti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…[15] Microencapsulation of sour cherries using maltodextrin and gum arabic with core to coating ratio 1 : 20 resulted in higher encapsulation efficiencies and smaller particle size than ration 1 : 10. [16] Microencapsulation of ascorbic acid using maltodextrin showed only 7% of ascorbic acid reduction in sample after stirage for 60 days at 28oC temperature. maltodextrin showed higer protection of bioactive compound compare with gum arabic, gum Arabic-modified starch (GA-MS), modified starch-chitosan (MS-CH) and modified starchmaltodextrin-chitosan (MS-MD-CH) (Chranioti et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This was the result of the high bonding capacity of inulin molecules. Lacerda et al (2016), in which they performed microencapsulation of jussara pulp with different coating materials, supported the formation of more intense agglomeration with SEM images by increasing the inulin concentration. Additionally, the most important parameters affecting the particle size are the nozzle frequency, feed rate, viscosity and surface tension of the feed solution (Masters, 1991).…”
Section: Resultsmentioning
confidence: 86%
“…Among the carriers tested, OSA starch was better able to preserve the bioactive compounds during atomization than native sorghum starch. This may be explained by the lipophilic succinyl moiety present in OSA starch structure that would simultaneously interact with polar and non‐polar bioactive compounds allowing better encapsulation of a wide variety of lipids and other lipophilic components . The results showed that spray drying process did not have any deleterious effect on antioxidant compounds.…”
Section: Resultsmentioning
confidence: 94%